2018
DOI: 10.3390/f9030139
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Picea abies and Pinus sylvestris Stumps with Urea and Phlebiopsis gigantea for Control of Heterobasidion

Abstract: Heterobasidion spp. root rot causes severe damage to forests throughout the northern temperate zone. In order to prevent Heterobasidion infection in summertime cuttings, stumps can be treated with urea or Phlebiopsis gigantea. In this study, the consumption of stump treatment materials and the quality of stump treatment work were investigated. A total of 46 harvesters were examined in May-November 2016 in Finland. The average stem size of softwood removal and softwood removal per hectare explained the consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Community differences between asymptomatic and symptomatic Heterobasidion -infected plant anatomies have also been studied ( 15 , 16 ). Antagonistic agents against Heterobasidion have also been broadly identified, providing microbial and mycobiota perspectives ( 17 , 18 ). However, most of the studies have shown the fragment of a single kingdom in the decay process, which might not be a true reflection of the full dynamics of the interaction within the microbiome community assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Community differences between asymptomatic and symptomatic Heterobasidion -infected plant anatomies have also been studied ( 15 , 16 ). Antagonistic agents against Heterobasidion have also been broadly identified, providing microbial and mycobiota perspectives ( 17 , 18 ). However, most of the studies have shown the fragment of a single kingdom in the decay process, which might not be a true reflection of the full dynamics of the interaction within the microbiome community assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Heterobasidion root rot caused by Heterobasidion annosum species complex is one of the most economically significant fungal diseases in the Northern Hemisphere . For prevention of spore infection of freshly cut stumps, stump surfaces can be treated with biological or chemical preparations (Kärhä et al, 2018). The Finnish BCA (biological control agent) Rotstop® containing oidia of Phlebiopsis gigantea is registered in Latvia and has been widely used since 2008 (Kenigsvalde et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Heterobasidion root rot has been found in pine trees in central Finland, which was previously solely common in southern Finland (Piri et al, 2021 ). Stump treatment using urea or Phlebiopsis gigantea is commonly used to prevent Heterobasidion infection (Kärhä et al, 2018 ). However, the prospect of using resistant genotypes obtained through breeding is a potential and durable approach to manage root and stem rot diseases.…”
Section: Introductionmentioning
confidence: 99%